PERILAKU HARIAN LUTUNG (Trachypithecus cristatus, Raffles 1812) DI PENANGKARAN PUSAT PENYELAMATAN SATWA GADOG, CIAWI-BOGOR - Wirdateti - -; Ai Nuri Pratiwi; Didit - Diapari; Anita S. - Tjakradidjaja (ZOO INDONESIA, 2009)
Wirdateti, A.N. Pratiwi, D. Diapari & A. S. Tjakradidjaja. 2009. Daily behavior offemale Leaf Grey Monkey (Trachypithecus cristatus, Raffles 1812) in WildlifeRescue Center Gadog captivity, Ciawi-Bogor. Zoo Indonesia 18(1): 33-40. Theresearch was conducted to study daily behaviour and feed preference of female leafgrey monkey (Trachypithecus cristatus, Raffles 1812) in captivity.Three female leafgrey monkeys were used in the study. Type of diets being oberserved were creepingwater-plant (Ipomea aquatica) forks, pohpohan (Pilea trinervia), spinach (Amaranthusspp. L), green brassica leaf (Brassica juncea, L), fruit-tree leaf (Gnetum gnemonLinn), and boiled sweet potato (Ipomea batatas Poir). The observation was conductedfrom 06.00 a.m to 06.00 p.m with 15 minutes interval time. Variables being measuredwere feeding activity, drinking activity, defecation, urination, locomotion, groomingand resting activity. Data were analyzed using descriptive analysis with one zerosampling method. The result showed that the percentage value of feeding activity,drinking activity, defecation, urination, locomotion, grooming and resting activity were:10.49%, 3.87%, 10.33%, 4.35%, 19.71%, 23.05% and 28.19% of total activities,respectively. Leaf grey monkey preferred to eat from the first until the last feeds, wereboiled sweet potato, green brassica, creeping water-plant, spinach and fruit-tree.